Challenges in the micropropagation of economically important fruit species in Europe - Sota, Valbona; Wilms, Hannes; Yücesan, Buhara; Mendi, Yeşim Yalçin; Christie, Bruce; Nisler, Jaroslav; Aslan, Şafak Esra; Purmale-Trasune, Liva; Silvestri, Cristian; Werbrouck, Stefaan P. O.; Fischerová, Lucie; Aronen, Tuija; et al. (Springer Nature, 2025)
Commercial micropropagation plays a crucial role in increasing the production of many economically important fruit crops worldwide, including Europe. The focus has been on many woody horticultural species, such as stone and pome fruits, berries, nuts, and palms. This paper presents an updated overview of the European commercial micropropagation landscape, highlighting the countries currently operating in this sector, crop targets, and the distribution of micropropagation companies based on recent survey data. In Europe and the broader Mediterranean basin, Italy, Spain, Türkiye, and Germany emerge as the leading contributors to the large-scale in vitro production of woody fruit species, based on the number of operating commercial companies and efforts to adopt new technology. Despite this progress, several challenges limit the scalability and sustainability of in vitro propagation systems, and their expansion in underrepresented countries. These main issues include species recalcitrance, high labour and infrastructure costs, further improvement of stock maintenance capacity, logistical issues in plantlet shipment, and barriers related to intellectual property rights. To address these challenges, this paper discusses solutions such as utilizing automation and robotics, exploring new compounds to enhance micropropagation rates, and using European funding opportunities. Furthermore, being involved in pan-European cooperation and technology transfer networks is also encouraged. The COST Action 21157 “CopyTree: European Network for Innovative Woody Plant Cloning” is discussed as a practical example of collaboration in harmonizing protocols for woody plant cloning and facilitating knowledge sharing among research groups with varying levels of experience in the field. Future advancements in the micropropagation sector will depend on the investment in automation and innovative technologies, combined with policy alignment with EU standards on a broader international level, and regional development strategies.
Keywords: micropropagation; woody fruit crops; commercial companies; in vitro propagation